Construcción naval de bajo bordo en el Perú: Periodo 2010-2016 - Schuler Frantzen, John (2021)
This article aims to describe the low board shipbuilding sector of Peru in the 2010-2016 period. The results of a scientific research based on a non-experimental, cross-sectional and descriptive methodology are shown with data provided by the Dirección General de Capitanías y Guardacostas. The article begins with a general and historical description of the sector, detailing the close relationship of this industry with the fishing sector. The results generally show an industry in recession with high levels of informality, the maritime shipbuilding sector in crisis and the river shipbuilding sector consolidating itself as the most important in the country's low-board shipbuilding.